Peran Lichen sebagai Bioindikator Pencemaran Logam berat Timbal (Pb) di udara - Jahja, Sukma Dewanty; Fitryane Lihawa; Dewi Wahyuni K. Baderan (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
The increase in human activities, such as industrialization, urbanization, and transportation, has led to air pollution, including heavy metal contamination such as lead (Pb). Lead originates from vehicle emissions, industrial activities, and fossil fuel combustion, which have detrimental effects on the environment and human health. One effective method for monitoring air pollution is biomonitoring using bioindicators, such as lichen. Lichen is sensitive to air quality and can absorb pollutants, including heavy metals, through its surface. This study uses a literature review to analyze the role of lichen as a bioindicator of heavy metal pollution, specifically lead. Several lichen species, such as *Xanthoparmelia xanthofarinosa* and *Canoparmelia aptata*, are known to accumulate heavy metals from the environment. The results show that the lead content in lichen varies depending on the pollution level in the location. Areas with high traffic have higher lead concentrations compared to areas with low traffic. The advantages of using lichen as a bioindicator include low cost, practicality, and its ability to provide long-term data on air quality. With this understanding, lichen data can be used for pollution mitigation and evidence-based policies to reduce the impact of air pollution. Further research is recommended to explore the potential of lichen in detecting other heavy metals, such as cadmium (Cd) and copper (Cu).